Improvement of dye-sensitized solar cell performance by utilizing graphene-coated TiO2 films photoanode. (April 2019) - Sadikin, S.N.; Rahman, M.Y.A.; Umar, A.A.; Aziz, T.H.T.
Abstract: Graphene-coated TiO2 films have been prepared via liquid phase deposition assisted with spin coating technique and employed as photoanode of dye-sensitized solar cell (DSSC). The effect of spin coating number of graphene films on the structural and optical properties of the sample has been investigated. The anatase TiO2 and graphene phase present in the sample. The optical absorption is high in UV region while its reflection is high in visible region. The morphological studies reveal that the TiO2 nanograss is coated with graphene sheet. The influence of the spin coating number on the performance of the device has also been investigated. The DSSC utilizing the sample prepared at 1 spin coating number demonstrates the highest power conversion efficiency, η of 1.47% and V oc of 0.66 V, respectively. Coating TiO2 films with graphene layer was found to improve the efficiency of the DSSC. Highlights: Graphene-coated TiO2 films have been employed as photoanode of dye-sensitized solar cells. The anatase TiO2 and graphene phase present in the sample. The morphological studies reveal that the TiO2 nanograss is coated with graphene sheet. The DSSC utilizing the sample prepared at 1 spin coating number demonstrates the highest η of 1.47%. Coating TiO2 films with graphene layer was found to improve the efficiency of the DSSC.